FAKTOR YANG MEMPENGARUHI PENGGUNAAN JENIS METODE KONTRASEPSI JANGKA PANJANG (MKJP) PADA WANITA MENIKAH USIA SUBUR DI PROVINSI JAWA TIMUR - Luki Triyanto; Diah Indriani (The Indonesian Journal of Public Health, 2018)
Long-Acting and Permanent Method (LAPM) is a very effective method of contraception, but women of childbearing age majority use short-term contraceptive methods. The purpose of this study was to apply multinomial logistic regression analysis in predicting factors affecting Fertile Women in the use of LAPM in East Java Province in 2012. This research use secondary data that was result of Indonesia Demographic Health Surveys (IDHS) year 2012 using the number of 171 respondents. The results of this study indicated the variables that affected the use of LAPM of WUS age (p = 0.008), education level (p = 0,004), occupation (p = 0,029), source of family planning services (p = 0,000), residence area (p = 0.016). The conclusion of this study was age, educational level, occupation, source of FP services, and residential areas affecting the use of long-term contraceptive methods in women of childbearing age. Therefore the government  through the National Family Planning Coordinating Board (BKKBN), still pay attention to the family planning program and ensure every community to implement family planning programs and educate and promote family planning programs to resolve the problems of the population.